Optimal Prediction of Weather Condition Based on C4.5 Classification Technique - Manikandan, M; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
In this world many of task is very challenged for researchers. By the way the accurate weather prediction is one of the disputes for the meteorologist. So this paper focuses the weather prediction for an implementing the classification technique of C4.5 Classification technique. This technique can be analyzed for the performance and accuracy of weather condition. Also this decision tree algorithm can be applied in weather prediction parameter of training data under the various regions. Such as, Tamil Nadu, Andra Pradesh, Gujarat and Odhisa states are taken from India for this research work. These states are mainly focus for the purpose of different monsoon seasons and climates vary from actual period of time. Finally, weather condition can be predicted on various monsoons seasonally on the respective class label of climate range